Coarsening evolution of dendritic sidearms: From synchrotron experiments to quantitative modeling. (March 2018) - Neumann-Heyme, H.; Shevchenko, N.; Lei, Z.; Eckert, K.; Keplinger, O.; Grenzer, J.; Beckermann, C.; Eckert, S.
Abstract: The local dynamics of dendritic sidearms during coarsening are studied by combining in-situ radiography observations with numerical and analytical models. A flat sample of a Ga-In alloy is partially solidified and then held isothermally in a vertical temperature gradient. The evolving dendritic microstructure is visualized using synchrotron X-ray imaging at the BM20 (ROBL) beamline at ESRF, France. During the coarsening stage, the temporal evolution of the geometrical features of sidebranches is captured by automated image processing. This data is then used to quantify the dynamics of two basic evolution mechanisms for sidebranches: retraction and pinch-off. The universal dynamics of sidearm necks during pinch-off are exploited to determine the product of liquid diffusivity and capillarity length D d 0, as a parameter that is crucial in the calibration of quantitative models. By employing an idealized phase-field model for the evolution of a single sidebranch, the behavior of selected sidebranches is reproduced from the experiments in a consistent way. Graphical abstract: Image 1